PRE-ROTATION OF SUTURE FAILURE DURING SUTURING OF PERFORATED GASTRIC AND DUODENAL ULCERS. - Professor Khakimov Murod Shavkatovich; PhD Ernazarov Khojimurod Irsaliyevich (Scholar Express Journals, 2025)
Improving the reliability of tightness of sutures when suturing perforated gastric and duodenal ulcers in conditions of widespread peritonitis by improving the method of preventing suture failure.
Keywords: Perforated Ulcer; Suturing Of Perforation; Nitric Oxide